ANALISIS GEOMORFOLOGI KEJADIAN LONGSOR DI KECAMATAN WOLOTOLO KABUPATEN ENDE - Sunimbar, Sunimbar; Angin, Ignasius Suban (Universitas Nusa Cendana, 2021)
The aimed of this research to determine the analysis of landslide in Wolotolo village, Detusoko district, Ende regency. This research used a survey method to map geomorphological conditions in Wolotolo Village, Detusoko District, Ende Regency. The method used in this research was a survey method to map geomorphological conditions in Wolotolo Village, Detusoko District. The main stages of this research include the pre-field, field and post-field stages. The pre-field stage was in the form of secondary data collection. The field stage was taking soil samples, identifying landslides in the field. The post-field stage was in the form of making landslides and reporting the results of field identification. The results of this research indicate that most of the soil types in Wolotolo Village wereultisols and inceptisols. This can caused this area to became an area that was prone to landslides. This study also found several dominant factors that may caused landslides, namely: slope, land use, soil type and rainfall as trigger factors. Steep slopes tend to be prone to landslides, especially with unstable slope conditions. This causes many steep slopes to be steep. Based on the results of the analysis, the slope in Wolotolo Village was more dominated by a slope of >45% which is a very steep area. So it can be identified that the area has the potential for landslides. Land use on steep slopes also affects slope stability. The land use in the study area is dominated by forest, plantations and shrubs.